OxaD, a versatile indolic nitrone synthase from the marinederived fungus Penicillium oxalicum F30 - Newmister, Sean A. (J Am Chem Soc, 2016)
Indole alkaloids are a diverse class of natural products known for their wide range of biological activities and complex chemical structures. Rarely observed in this class are indolic nitrones, such as avrainvillamide and waikialoid, which possess potent bioactivities. Herein the oxa gene cluster from the marine-derived fungus Penicillium oxalicum F30 is described along with the characterization of OxaD, a flavin-dependent oxidase that generates roquefortine L, a nitrone-bearing intermediate in the biosynthesis of oxaline. Nitrone functionality in roquefortine L was confirmed by spectroscopic methods and 1,3-dipolar cycloaddition with methyl acrylate. OxaD is a versatile biocatalyst that converts an array of semisynthetic roquefortine C derivatives bearing indoline systems to their respective nitrones. This work describes the first implementation of a nitrone synthase as a biocatalyst and establishes a novel platform for late-stage diversification of a range of complex natural products.